The Effectiveness of Reality Therapy on Healthy Lifestyle and Self-Care Indicators of Women with Type 2 Diabetes - Shahnavazi , Abdolvahed; Sedaghat, Mastooreh; Sabet, Mehrdad (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The aim of this study was the effectiveness of reality therapy on lifestyle and self-care characteristics of women with type 2 diabetes. Methods: The method of this study was quasi-experimental with pre-test-post-test and follow-up design with control group. The statistical population of the study consisted of women with type 2 diabetes referred to diabetes clinic of Zahedan University of Medical Sciences in 2019, among whom 40 patients were selected by voluntary available sampling method and were assigned to reality therapy (n=20) and control group (n=20). Glasser reality therapy training was performed in 10 sessions, 90 minutes and the control group did not receive any training. The follow-up period was performed two months after the end of the sessions. Data were obtained through lifestyle questionnaire Melby, Hyner, & Zoog (1985) and self-care behaviors questionnaire Lee et.al (2010). Data were analyzed using repeated variance analysis and SPSS.22 software. Results: The results showed that the effectiveness of reality therapy on healthy lifestyle (P